2012
DOI: 10.1017/s1049023x12001331
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Willingness of Health Care Personnel to Work During an Influenza Public Health Emergency: An Integrative Review

Abstract: Understanding the factors that contribute to the willingness of HCP to report to work during an influenza public health emergency is critical to emergency planning and preparedness. Information from this review can guide emergency policy makers, planners, and implementers in both understanding and influencing the willingness of HCP to work during an influenza public health emergency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
112
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(123 citation statements)
references
References 43 publications
6
112
2
3
Order By: Relevance
“…Other studies have also shown the importance of this characteristic at the time of a surge (24, 25). …”
Section: Discussionmentioning
confidence: 87%
“…Other studies have also shown the importance of this characteristic at the time of a surge (24, 25). …”
Section: Discussionmentioning
confidence: 87%
“…Results from several studies suggest that training is linked with greater effectiveness of emergency response efforts and that training of health personnel is positively associated with willingness to volunteer and deploy in the event of a disaster [2-4]. However, there exist several significant gaps in training for emergency providers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed meaningful disparities in response willingness during an influenza pandemic among varied responder cohorts. 9,10 For example, a study of local health department workers in Florida (USA) found that approximately 29% were not willing to report to work during the peak period of an influenza pandemic if their responsibilities included face-to-face contact. 11 In a survey of hospital workers in Maryland (USA), 28% were not willing to report to work during an influenza pandemic if asked.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that there would be an association between presence of the state-level emergency preparedness laws of interest and willingness to respond among EMS workers was based on previous research. 5,6,8,9,12 Methods…”
Section: Introductionmentioning
confidence: 99%